(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, we discuss the importance of railway transportation in New Uzbekistan, which remains a fundamental transport type and is expected to maintain its role in the foreseeable future. The significance of railway transit is increasing due to the growing movement between China, Russia, and the Central Asian states, especially with Uzbekistan’s landlocked position and China’s active development of the "New Silk Road" initiative. Therefore, it is crucial to examine the problems and prospects of developing the railway infrastructure in our country. Trends in the development of railway transport and quality theory in this field have been studied and reviewed. The efficiency of transportation processes and their impact on production and living standards were analyzed. Proposals were made to improve the economic efficiency of railway transport divisions’ production and economic activities.